PROSEDUR ADMINISTRASI PELAYANAN JASA TICKETING PENERBANGAN, TOUR PACKAGE, DAN PENYEWAAN ALAT TRANSPORTASI PADA PT. JODIREXA JAYA ADITAMA - Rafli Rahmadika; Shelsa Djuliani Putry; Siti Nur Aisyah; Muhamad Andri Ardiansyah; Raihan Rafi Rizkuloh; Nur Azizah; Dyah Bayu Framesthi (LPPM Politeknik Pajajaran ICB Bandung, 2026)
This study aims to analyze the administrative procedures involved in providing flight ticketing services, travel packages, and transportation rental at PT Jodirexa Jaya Aditama, a travel agency company. The research emphasizes the administrative workflow, the implementation of digital systems, and the influence of human resource constraints on service effectiveness. The research employs a qualitative descriptive approach, with data collected through direct observation, interviews with administrative staff, and documentation studies of internal company records. The findings reveal that PT Jodirexa Jaya Aditama has adopted structured administrative procedures for each service, particularly by utilizing airline digital platforms and employing standard formats in the design of travel packages. Nevertheless, the administrative procedures for these three services are often managed by the same staff and continue to operate separately, potentially resulting in high workloads and risks of operational errors. Consequently, initiatives for more effective standardization and integration of administrative procedures are required to sustainably enhance service quality and bolster the operational efficiency of the tourism service company.